A ANALISIS CR, DAR, DER, NPM, ROA DAN ROE TERHADAP PERTUMBUHAN LABA PERIODE TRIWULAN DARI TAHUN 2016-2022 ((Studi Pada PT Telekomunikasi Indonesia Yang Terdaftar Di BEI)) - Febrianti, Dian; Wuryanti, Lestari; Indriani, Wiewiek (Journal of Development Economics and Digitalization, Tourism Economics, 2024)
Profit growth is an increase in company profits compared to previous period earnings Good company profit growth reflects that the condition of the company's performance is also good, if the economic conditions are good the company's growth is generally good. Because profit is a measure of the performance of a company, the higher the profit achieved by the company, indicates the better the company's performance, thus investors are interested in investing their capital. ZThe object in this study is PT Telekomunikasi Indonesia Tbk which is listed on the IDX for the Quarterly Period from 2016-2022. The sampling method in this study used nonprobabilin sampling with purposive sampling. The results of this study stated that partially the CR variable had a significant negative effect on profit growth, while the DAR, DER NPM, ROA and ROE variables partially had no effect on profit growth simultaneously with the CR variable. DAR DER NPM ROA and ROE affect profit growth at PT Telekomunikasi Indonesia Tbk which is listed on the IDX Quarterly period from 2016/2022